Nutritional Intervention Model (Probiotics and Prebiotics) to Address Stunting Problems in Toddlers - Waifti Amalia; Senditya Indah Mayasari (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Stunting is a chronic nutritional problem that impairs child growth. Its main causes include inadequate dietary intake and recurrent gastrointestinal infections. Probiotic and prebiotic–based interventions are believed to improve gut function and enhance nutrient absorption. This study applied a pre–post test design involving 15 stunted toddlers. The intervention consisted of locally sourced foods containing probiotics and prebiotics, administered for 14 days. Data collection included body weight, height, and Z-scores, measured before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test. The mean body weight increased by 0.25 kg (p=0.001), while height increased by 0.64 cm (p=0.001). The weight-for-age Z-score improved by 0.27, and the height-for-age Z-score improved by 0.23. All participants demonstrated positive changes, with no decrease observed. Locally sourced foods containing probiotics and prebiotics were proven effective in improving body weight and height among stunted toddlers. This approach offers a simple, affordable, and practical nutritional strategy for the prevention and management of stunting at the community level.